"More Advantageous to Be with Spaniards": Gunpowder and Creek–Spanish Encounters in Cuba, 1763– 1783. (1st September 2020) - Monroe McCutchen, Jennifer
Abstract : This research investigates Creek Indian and Spanish encounters in Cuba, exploring the ways in which Natives looked beyond the Southeast for access to commodities following the Seven Years' War. It uses gunpowder as a lens to examine how ongoing Creek–Spanish relations shaped gender dynamics, personal relationships, local-level politics, and cultural structures within the Confederacy while simultaneously impacting Spanish geopolitics in the Atlantic World. This research seeks to better understand how Creek efforts to acquire gunpowder through formal processes of encounter and exchange in Cuba benefited both the aims of Indigenous leaders and Spanish officials during an era of change for both cultures.